Desarrollo de un modelo computacional basado en arquitectura orientada a modelos para la transformación de un diagrama de clases en código fuente java - Díaz Fernández, Pedro Pablo (2016)
In this research paper entitled "Development of a system based on Oriented Architecture Models for Transformation of a Class Diagram to Source Code Java Computational Model", we propose an algorithm for improving the processing of class diagrams to source code as for the time and complexity, based on models oriented architecture._x000D_ For this research 8 different models Transformation Class Diagrams to Java Source Code were analyzed; which analyzes one to one obtaining the advantages and disadvantages. With them we start with the development of the model we eventually propose._x000D_ The proposed computational model consists of 3 phases: Modeling, Trial and Transformation. In the first phase the Class Diagram is used to formalize the necessary data are then used in the next phase of Instance. In this second phase, the metamodel class is used so that, from this, to create an instance; It is at this stage where we also began to focus on the Model to Oriented Architecture Models, spent the Model PIM to PSM. Finally, in the phase of transformation, using the instance created in the previous phase to transform it into Java source code; at this stage we PSM Model Code._x000D_ As a result of this process the desired coding is obtained by improving the time to transform class diagrams to their respective Java source code